Strategi Pengembangan Bisnis UMKM Seni Lukis di Kampung Seni Jelekong, Bandung - Oktapian, Elsa; Wijaya, Fanji; Herlinawati, Erna; Mubarok, Dadan Abdul Aziz (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study aims to analyze the development of painting UMKM in Kampung Jelekong, Bandung, focusing on marketing strategy and SWOT analysis. Painting UMKM has great potential to develop and positively contribute to the local economy. However, they are also faced with various challenges in marketing their painting products and competing with an increasingly tight market. This research uses a qualitative approach with the case study method to collect data from various sources, including interviews with painting UMKM owners, field observations, and analysis of related documents. The collected data is then analyzed to identify opportunities and obstacles in developing the painting UMKM in Jelekong Village. The analysis results show that marketing strategies play an important role in driving the growth of painting UMKM. The keyword